Isolation of Bacillus spp. from rhizosphere of garden soil: their potential role in amylase production and nitrogen cycle (Stamford Journal of Microbiology, 2020)
Rhizobacteria influence plant growth by producing various substances like enzymes and play role in nitrogen cycle. Microbes are the most important sources of enzymes because of their stability and reduced price in production. In our present investigation, soil samples were collected from rhizosphere of garden soil and a total of eight isolates of Bacillus spp. were presumptively identified by morphological, cultural and biochemical analysis with the conventional technique. The isolates were named as A1, A3, A4, A5, B2, C1, D1 and D2. Amylase enzyme assay was performed by 3, 5-dinitrosalicylic acid method. The highest enzyme activity was observed with the isolate A4 (2.71 U/ml) followed by isolates D2 (2.54 U/ml) and D1 (2.52 U/ml). The highest ammonification was found to be positive with the isolates A4 and B2 followed by isolate D1. Denitrification potential was found to be highest with isolates A4 and A5. No isolates were found to fix atmospheric nitrogen in Jensen’s media after two weeks of incubation. The isolates have a great potential of amylase production and they can be used in different industries as well as in starch rich waste degradation. Involvement of these bacteria in nitrogen cycle may help promote growth of plants.Stamford Journal of Microbiology, Vol.10 (1) 2020: 12-15